Reduction in Posttraumatic Stress Symptoms in Congolese Refugees Practicing Transcendental Meditation. Issue 2 (8th April 2013) - Rees, Brian; Travis, Fred; Shapiro, David; Chant, Ruth
<x xml:space="preserve">Abstract</x> This matched single‐blind pilot study tested the effect of Transcendental Meditation® (TM) practice on symptoms of posttraumatic stress (PTS) in Congolese refugees. Urban refugees (N = 102) staying around Kampala, Uganda attended introductory meetings. After initial random assignment to the TM group, 30 refugees who revealed that they were unable to attend all meetings and were eliminated from the study. The remaining 21 TM group participants were then instructed in TM and matched with refugees in the control group on age, sex, and baseline scores on the Post‐traumatic Stress Disorder Checklist–Civilian (PCL‐C). All participants completed the PCL‐C measure of PTS symptoms at baseline, and 30‐day and 135‐day posttests. The PCL‐C scores in the control group trended upward. In contrast, the PCL‐C scores in the TM group went from 65 on average at baseline indicating severe PTS symptoms to below 30 on average after 30 days of TM practice, and remained low at 135 days. Effect size was high (d > 1.0). Compliance with TM practice was good; most reported regular practice throughout the study. There were no adverse events. All refugees who learned TM completed the study and were able to practice TM successfully, with subsequent substantial reduction in PTS symptoms.